Antibiotic Prescribing Patterns for Acute Otitis Media for Children 2 Years and Older - Frost, Holly M. (J Pediatr, 2020)
OBJECTIVE: To determine the frequency that non-first-line antibiotics, safety-net antibiotic prescriptions (SNAPS), and longer than recommended durations of antibiotics were prescribed for children ≥2 years of age with acute otitis media and examine patient and system level factors that contributed to these outcomes. STUDY DESIGN: Children age ≥2 years with acute otitis media seen at Denver Health Medical Center outpatient locations from January to December 2018 were included. The percentages of patients who received first-line antibiotics, SNAPs, and recommended durations of antibiotics were determined. Factors associated with non-first-line and longer than recommended antibiotic durations were evaluated using multivariate logistic regression modeling. RESULTS: Of the 1025 visits evaluated, 98.0% were prescribed an antibiotic; only 4.5% of antibiotics were SNAPs. Non-first-line antibiotics were prescribed to 18.8% of patients. Most antibiotic durations (94.1%) were longer than the institution recommended 5 days and 54.3% were ≥10 days. Private insurance was associated with non-first-line antibiotics (aOR, 1.89; 95% CI, 1; 14-3.14, P = .01). Patients who were younger (2-5 years; aOR2.01; 95% CI, 1.32-3.05; P < .001) or seen in emergency/urgent care sites (aOR, 1.73; 95% CI, 1.26-2.38; P < .001) were more likely to receive ≥10 days of antibiotic compared with those in pediatric clinics. CONCLUSIONS: Antibiotic stewardship interventions that emphasize the duration of antibiotic therapy as well as the use of SNAPs or observation may be higher yield than those focusing on first-line therapy alone. Numerous system and patient level factors are associated with off-guideline prescribing.